Inactivation of protein‐phosphatase 2A causing hyperphosphorylation of autoantigenic paraprotein targets in MGUS/MM is due to an exchange of its regulatory subunits. Issue 9 (5th April 2014) - Preuss, Klaus‐Dieter; Fadle, Natalie; Regitz, Evi; Held, Gerhard; Pfreundschuh, Michael
<x xml:space="preserve">Abstract</x> Hyperphosphorylated paratarg‐7 (pP‐7) carrier state is the strongest molecularly defined risk factor for monoclonal gammopathy of undetermined significance (MGUS), multiple myeloma (MM) and Waldenstrom's macroglobulinemia (WM). pP‐7 is inherited as autosomal‐dominant trait and depending on the ethnic background is found in over one‐third of MGUS/MM patients. P‐7, which is the antigenic paraprotein target in these patients, is hyperphosphorylated at serine17. P‐7 hyperphosphorylation can be induced in wild‐type P‐7 (wtP‐7) carriers by PKCζ and reverted by protein‐phosphatase 2A (PP2A). Here we show that dephosphorylation of pP‐7 is defective in pP‐7 carriers due to inactivation of the PP2A by substitution of the regulatory B55δ subunit with B56γ3. In lymphoblastoid cell lines from pP‐7 carriers, transfection of recombinant B55δ or treatment with ceramide led to a partial reconstitution of PP2A activity and dephosphorylation of pP‐7 to wtP7. Similar results were observed with other previously reported autoantigenic paraproteins targets. In conclusion, the mechanisms responsible for the defective dephosphorylation and maintaining the hyperphosphorylated state of P‐7 and other autoantigenic paraprotein targets have been elucidated, facilitating the identification of the genetic basis underlying this phenomenon which is obviously common in the pathogenesis of MGUS/MM/WM and not restricted to pP‐7 cases.